2005
DOI: 10.1080/09548980500254654
|View full text |Cite
|
Sign up to set email alerts
|

The development of retinotectal maps: A review of models based on molecular gradients

Abstract: Information about the world is often represented in the brain in the form of topographic maps. A paradigm example is the topographic representation of the visual world in the optic tectum/superior colliculus. This map initially forms during neural development using activity-independent molecular cues, most notably some type of chemospecific matching between molecular gradients in the retina and corresponding gradients in the tectum/superior colliculus. Exactly how this process might work has been studied both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
63
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 140 publications
0
63
0
1
Order By: Relevance
“…Do the two maps share similar mechanisms of development? Previous studies suggest that the visual map in the superior colliculus (SC; the mammalian homologue of the OT) is capable of developing independent of visual experience, relying on molecular gradients (Goodhill and Xu 2005) and spontaneous activity (Katz and Shatz 1996). Dark-rearing experiments in rats demonstrated that visual experience is important for maintenance but not for the development of the visual map in the SC (Carrasco et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Do the two maps share similar mechanisms of development? Previous studies suggest that the visual map in the superior colliculus (SC; the mammalian homologue of the OT) is capable of developing independent of visual experience, relying on molecular gradients (Goodhill and Xu 2005) and spontaneous activity (Katz and Shatz 1996). Dark-rearing experiments in rats demonstrated that visual experience is important for maintenance but not for the development of the visual map in the SC (Carrasco et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The extensive experimental and theoretical investigation of the development of topographically ordered maps from the retina to its targets ( Figure 1A) has led to two important theories of map development: molecular signalling and activity-dependent synaptic plasticity (Goodhill & Xu, 2005). In theories of molecular signalling, retinal ganglion cell (RGC) growth cones bear receptors in different densities depending on the location of the RGC soma in the retina, and these receptors are activated by ligands expressed in cells in the superior colliculus (SC) at levels depending on their location.…”
mentioning
confidence: 99%
“…Insights from experiments with mutant mice gave rise to new computer models, several of which have been reviewed (Swindale, 1996;Goodhill and Richards, 1999;Goodhill and Xu, 2005;Goodhill, 2007). However, these reviews were qualitative and excluded recent genotypes (Cang et al, 2008;Triplett et al, 2011).…”
Section: Introductionmentioning
confidence: 99%